Effect of Surgical Findings on Prediction of Postoperative Ovarian Reserve in Patients with Ovarian Endometrioma - Lee J; Kang J; Lee HJ (Dove Medical Press, 2022)
Jisun Lee, Juyeon Kang, Hyun Jung Lee Department of Obstetrics and Gynecology, School of Medicine, Kyungpook National University, Kyungpook National University Hospital, Daegu, Republic of KoreaCorrespondence: Hyun Jung Lee, Department of Obstetrics and Gynecology, School of Medicine, Kyungpook National University, Kyungpook National University Hospital, 130, Dongdeok-ro, Jung-gu, Daegu, 41944, Republic of Korea, Tel +821035328741, Fax +82534237905, Email hyunjunglee@knu.ac.krObjective: Revised American Society for Reproductive Medicine (rASRM) classification for endometriosis is considered to have limited ability to predict fertility after surgery. This study evaluated the effect of surgical findings described by the rASRM classification on postoperative change in serum Anti-Müllerian hormone (AMH) in endometriosis.Study Design: We retrospectively analyzed 112 patients with endometrioma who underwent laparoscopic ovarian cystectomy. The ovarian score was defined as the sum of the endometrioma score from the size and depth of endometrioma and the adhesion score from the extent and types of ovarian adhesion described in the rASRM classification. The ovarian score was correlated with the AMH levels before surgery (AMH0), 3 (AMH3), and 6 months (AMH6) after surgery. To design a model for predicting AMH6, using ovarian score and AMH0, we calculated the unstandardized predictive value of AMH6/AMH0 (UPV) by linear regression analysis. The predicted AMH6 (pAMH6) could be calculated by multiplying the UPV by AMH0. When AMH6 is less than 1.0 ng/mL, it was defined as a poor ovarian reserve group (PORG), and the accuracy of the predictive model was validated.Results: The level of AMH declined more in rASRM stage IV compared to stage III after surgery. The ovarian score had a significant variable in the linear regression analysis with the ratio of AMH6/AMH0 (p = 0.001). The UPV was correlated with ovarian score negatively. The pAMH6 correlated with AMH6 positively and with age negatively. The pAMH6 showed sensitivity 0.564, specificity 0.909, positive predictive rate 0.786, and negative predictive rate 0.800 in the prediction of PORG (p < 0.001).Conclusion: The pAMH6 predicted the PORG at 6 months after surgery. Based on the results of our study, the surgical findings, including the size and depth of the endometrioma and extent and types of adhesion could be useful indicators for ovarian reserve after surgery.Keywords: endometrioma, anti-Müllerian hormone, ovarian reserve, cystectomy, revised American Society for Reproductive Medicine (rASRM) classification